DES modified silica gel as dispersing material for miniaturized matrix solid phase dispersion applied to triazoles determination - Susanna Della Posta; Valeria Gallo; Emanuele Limiti; Marcella Trombetta; Monica Gherardi; Alessandra Gentili; Laura De Gara; Chiara Fanali (Advances in Sample Preparation)
Matrix solid phase dispersion (MSPD) represents one of the most useful methods for pesticides determination in vegetables. This extraction method involves the use of a solid, dispersing material, which is homogenized together with the sample in a mortar and loaded into a cartridge for the analyte's elution with a suitable solvent. Innovative MSPDs involve the use, as dispersing material, of silica gel (SCG) impregnated with deep eutectic solvents (DESs). SCG high porosity can facilitate DES impregnation process due to hydrogen bonds or electrostatic interactions among them.A miniaturized MSPD extraction for triazoles from tomato using as dispersant DES modified SCG, followed by HPLC-MS extracts analysis, was developed. Four DES modified SCGs were tested in the MSPD procedure and the best result in terms of extracted triazoles was obtained using a choline chloride – Propylene Glycol DES modified SCG. Ethyl Acetate was selected as MSPD procedure extractive solvent resulting more efficient than methanol, acetonitrile and chloroform. The optimization of the extraction procedure involved the study of SCG to DES ratio (w/v), sample to dispersing material ratio (w/w) and extractive solvent volume able to obtain the greatest recovery of triazoles from tomato. The optimized method was validated and maximum values of 3.6 % and 8.3 % were obtained for intra-day and inter-day precision respectively. For each analyte the calculated limit of quantification was similar or lower than their Maximum Residue Limit. Triazoles mean recovery ranged from 70 to 102 %.The new ChCl-propylene glycol DES modified SCG represents a valid alternative to conventional dispersing material in MSPD procedure apply to pesticides determination.